VLIDORT-QS: A quasi-spherical vector radiative transfer model. (November 2022) - Spurr, R.; Natraj, V.; Colosimo, S.F.; Stutz, J.; Christi, M.; Korkin, S.
Highlights: Spherical atmosphere. Multiple scattering of solar light. Polarization. Validation of radiative transfer software. Abstract: We present a new VLIDORT-based quasi-spherical vector radiative transfer (RT) model (VLIDORT-QS) that was developed for forward-model simulations of long-path measurements in limb- or nadir-viewing spherical-atmosphere configurations. This paper provides a theoretical description of the RT model, in which the single-scatter radiation field is treated accurately in spherical geometry, while the diffuse-scatter source terms at points along the line-of-sight are approximated locally through pseudo-spherical simulations based on the VLIDORT RT code; these multiple scatter source terms are then folded into the source function integration to yield the radiation field at any line-of-sight observation point in the atmosphere. In addition, the VLIDORT-QS model has a complete linearization facility (ability to generate analytic Jacobians of the radiation field with respect to any atmospheric or surface property). Validation of the model has been carried out against a fully-spherical Monte Carlo code, and also against the standard VLIDORT model for nadir-view scenarios with relatively low sphericity effects. A sample application of VLIDORT-QS for a biomass-burning plume scenario is demonstrated. A second paper will present a detailed analysis of the retrieval of ice-cloud properties from high-altitude aircraft measurements taken as part of the NASA Airborne Tropical Tropopause Experiment (ATTREX) campaign, with VLIDORT-QS providing forward-model simulations of the radiation fields and associated Jacobian functions.